Mallow and plantain flowers - Lindquist, Mark, photographer (Colorado State University. Libraries, 2009)
Orange SPCO, Sphaeralcea coccina, flowers next to (wooly) plantain in flower on the SGS.
Keywords: SGS; flowers; plants